Effects of Tibolone on Bone Mass in Postmenopausal Women - Snezana Maric KREJOVIC,; Aleksandar ZIVANOVIC,; Bajram HASANI,; Tatjana ILLE,; Andrea GLISIC5, (Archives of Rheumatology, 2011)
Objectives: We aimed to investigate the effects and tolerability of tibolone treatment in women with postmenopausal osteoporosis. Patients and methods: Patients received tibolone tablets orally once a day after receiving strict instructions. All patients received calcium supplementation with 500 mg of active calcium, and 400 IU of vitamin D. For the purpose of this study, 93 women who received tibolone for two years were examined. They comprised the study group. The second group included 33 women with osteoporosis who received only a supplement of 500 mg of active calcium and 400 IU vitamin D. The third group (control) was composed of 42 women with osteoporosis who took no medication if advised to do so. Bone mineral density was measured at the lumbar spine, and measurements were performed prior to treatment, after one year, and after two years of treatment using the dual energy X-ray absorptiometry method. The bone mineral density was examined in the group of 33 women taking calcium and vitamin D and in the group taking no medication. Results: A 4.9% improvement in bone mass was registered after a year of treatment with tibolone, and there was a 7.5% improvement after two years. In patients receiving calcium and vitamin D, a significant increase in bone mass of 2.9% occurred as well after a year, but the values returned to the baseline level after the second year. In patients without any treatment, the bone mass decreased by 0.6% after a year and by 0.9% after the second year. Conclusion: Our two-year study of the efficacy and tolerability of tibolone in women with osteoporosis confirmed that tibolone significantly increases vertebral bone mass with good tolerability. This finding indirectly implies that the risk of both vertebral and non-vertebral fractures is also significantly reduced.